Effects of 12‐month exercise intervention on physical and cognitive functions of nursing home residents requiring long‐term care: a non‐randomised pilot study. Issue 4 (4th February 2020) - Tsugawa, Akito; Shimizu, Soichiro; Hirose, Daisuke; Sato, Tomohiko; Hatanaka, Hirokuni; Takenoshita, Naoto; Kaneko, Yoshitsugu; Ogawa, Yusuke; Sakurai, Hirofumi; Hanyu, Haruo
Abstract : Aims: We performed a 12‐month exercise intervention for 'nursing home for the elderly' residents requiring long‐term care. We evaluated changes in their muscular strength, muscle mass, and cognitive function. Methods: Thirty‐seven nursing home residents (Mini‐Mental State Examination (MMSE): 14.7 ± 7.0, Barthel Index: 44.2 ± 18.9) were enrolled. We divided the participants into the exercise intervention group ( n = 19) and non‐intervention group ( n = 18) ensuring no significant difference in the participants' characteristics at baseline. For the exercise intervention group, exercise was performed for about 40 min twice a week for 12 months. Skeletal Mass Index and grip force were determined to evaluate muscle mass and muscle strength, respectively. MMSE, Trail Making Test (TMT) part A, and Geriatric Depression Scale 15 (GDS15) were used for cognitive function evaluation, with their changes investigated. Results: After 12 months, the MMSE scores were significantly improved in the exercise intervention group compared with the non‐intervention group (change from baseline to 12 months: Non‐intervention: −1.0 ± 2.8, Intervention: 1.2 ± 3.0; P = 0.04). Moreover, the grip force of the dominant arm was significantly improved in the exercise intervention group compared with the non‐intervention group (change from baseline to 12 months: Non‐intervention: −1.3 ± 2.8 kg, Intervention: 1.4 ± 4.6 kg; P = 0.007). The prevalence of sarcopenia was significantly increased after 12 months compared with baseline in the non‐intervention group (Non‐intervention: 61.1% → 75.0%, Intervention: 77.8% → 71.4%; P < 0.02). There were no significant changes in GDS15, Barthel Index and TMT after 12 months in intervention and non‐intervention groups. Conclusion: Exercise intervention may be effectively used for improving the physical and cognitive functions of nursing home residents requiring long‐term care.